Influence of carnichrome® on energy balance of gestating sows - M G Young; J Noblet; F X Aherne; Milgen J Van; J C Woodworth; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2003)
Twelve multiparous sows were utilized in a randomized complete block design to determine the effects of feeding diets with or without Carnichrome® (50 ppm carnitine and 200 ppb chromium picolonate) on the components of heat production (HP) in early, mid and late gestation. All sows were fed dietary treatments for the 28 d lactation, and the subsequent weaning to estrus and gestation periods. The kinetics of HP and its partitioning (basal or resting HP, activity HP, and short term thermic effect of feeding (TEFst)) were determined during three stages of gestation, early (weeks 5 or 6), mid (weeks 9 or 10) and late (weeks 14 or 15) for each block. Feeding allowances were based on modeled calculations of energy and nutrient requirements to achieve a target sow maternal weight gain of 44 lb and remained constant throughout gestation. On d 111 of gestation sows were slaughtered and total uterus, individual fetal, placenta and empty uterus weights were recorded. Organic matter and energy digestibility for the Carnichrome® diet was greater (P<0.05) and fecal N excretion was lower (P<0.05), which resulted in the DE and ME content of the Carnichrome® diet being greater (P<0.05) compared to the control diet. Carnichrome® had no effect on total HP, energy retained as protein or lipid or maternal energy retention in early, mid or late gestation. Increased HP in late gestation was associated with increased uterine energy requirements. The ME intake on d 110 of gestation was 6.9 Mcal/d, but to prevent sows from mobilizing maternal tissues ME intake would need to be increased to 8.4 Mcal/d. This equates to a 21.5% increase in ME intake or an additional 1 lb/d of a corn soybean meal diet on d 110 of gestation than fed in the present experiment. Energy requirements for maintenance averaged 91 kcal/kgBW0.75/d, and was greater in late compared with mid-gestation in the present experiment. On average 20% of ME intake was utilized for physical activity but ranged from 11.6 to 37.1%. Each 100 minutes of standing time/day represented an additional requirement of 0.38 lb/d of a standard corn soybean meal diet (1485 kcal/lb). The results of the present experiment indicate that improvements in reproductive performance found in previous experiments with carnichrome do not appear to be due to changes in heat production or improvements in energy retention. In conclusion, Carnichrome® had no effect on the components of heat production and maternal weight gain during early-, mid- or lategestation, but did improve energy and organic matter digestibility of the diet.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Sows; Carnichrome®; Heat production; Gestation; Swine